Design and experiment of coconut picking robot with climbing - Hongcheng Zheng; Yuxing Fu; Zongbin Wang; Xinjie Yin; Yuyang Xia; Wei Fu (Smart Agricultural Technology)
Due to the height of coconut trees and the high risks associated with manual picking, there is a severe shortage of labor in the coconut picking industry in Hainan. To address this issue, a coconut picking robot was designed and constructed. In this study, the robot was mainly composed of tree climber and 3 degree of freedom (DoF) manipulator. The robot integrated two functions of tree climbing and coconut picking. The 3D model of the picking robot was designed through SOLIDWORKS. Furthermore, the statics and dynamics simulation of the robot were implemented through ANSYS and ADAMS. With STM32 as the core, an embedded remote control system based on CAN bus communication protocol was developed. And a multi-channel remote controller handle was used to control the robot to realize tree climbing and coconut picking. According to the test results, the robot could successfully climb trees up to 13.42 m tall. The average climbing time of coconut picking robot on 10 coconut trees was 152.3 s, and the average picking time was 222.1 s. Specifically, for coconut trees with height ranging from 7.03 m to 11.5 m, inclination ranging from 78° to 90° and diameter ranging from 21.08 cm to 30.20 cm, the average climbing time of the coconut picking robot was 147.7 s. The average climbing time for the remaining trees was 162.9 s. For the above types of trees, the robot could climb to the top of the trees more quickly, demonstrating better climbing performance. This study provides technical support for mechanized coconut picking and will inspire the development of coconut picking robots.